Prosecuting international crimes : selectivity and the international criminal law regime - Cryer, Robert (Cambridge studies in international and comparative law (Cambridge, England : 1996), 2005)
This book concentrates on the legitimacy of the international criminal law regime. It explains the development of the system of international criminal law enforcement in historical context, with regard to international relations theory.